Lahan Pertanian Abadi (LPA) Di Kabupaten Tangerang - Yunita Ismail (Bina Nusantara University, 2011)
Tangerang regency is a supporting area for DKI Jakarta. The main function of this supporting area is as the human resource for fulfilling development needs of DKI Jakarta. Based on agricultural products from Tangerang regency, it is known that rice production almost 12 tons GKP/ha/year. This production is big enough to support harvest production nationally. Therefore, changing in dedicated agricultural field to be a non-agricultural area is considered will decrease rice production in Tangerang regency. Based on those conditions, it is needed to decide agricultural field which will not be used for non-agricultural activities, or so called agricultural land conversion (LPA). This research uses secondary data from Biro Pusat Statistik (Indonesia bureau of statistic) in Tangerang regency. The conclusion is that controlling the agricultural land conversion based on land capability survey in LPA area, as detail survey to irrigated rice field, non-irrigated rice field, and deep observation for agricultural field non-rice field.